Peningkatan Keterampilan Menyimak Cerita Fabel Menggunakan Media Audiovisual di SDN Diwek 1 Jombang - Endah Sari (MAN Insan Cendekia Jambi, 2025)
Listening ability is an important basic skill in mastering Indonesian, but in realities many elementary schoolstudents still have difficulty in understanding the contents of the story, especially in recognizing elements of theplot, characters, and moral messages. One of the causes is the use of conventional learning models that are lessinteresting. This study aims to improve students' listening skills in understanding fable stories through the useof audiovisual media at SDN Diwek 1 Jombang. The background of this study is based on the low ability ofelementary school students in understanding story elements such as plot, characters, and moral messages whenlearning is carried out conventionally. This study used a quasi-experimental method with a pretest-posttestcontrol group design. The sample in this study was 27 fifth grade students at SDN 1 Diwek. The instrument usedwas a listening test. The results showed that there was a significant increase in students' posttest scores. Thisshows that audiovisual media is effective in improving listening skills and understanding the contents of fablestories. The novelty of this study lies in the integration of audiovisual media with the local learning context andthe emphasis on the characteristics of generation Z students who are more responsive to visual and interactivemedia. These findings suggest that the application of audiovisual media in story listening activities can be apowerful learning strategy at the elementary education level.